Heart valve tissue engineering for valve replacement and disease modeling. (March 2018) - Zhu, Amadeus S.; Grande-Allen, K. Jane
Abstract: Heart valve tissue engineering is emerging as a promising method for constructing both valve replacements and valvular disease models. Tissue-engineered valve replacements strive to overcome the limitations of mechanical and bioprosthetic valves, because they are living tissues capable of active remodeling and self-repair. Several tissue-engineered valve replacements have displayed promising results in recent large-animal trials. On the other hand, tissue-engineered disease models provide a scalable platform for investigating the pathobiology of valvular diseases like aortic stenosis. Recently, these models have been used to study the role of spatial heterogeneity, temporal matrix stiffening, and inter-cellular signaling in valve disease. This review provides an overview of recent developments, current challenges, and future directions in the field of heart valve tissue engineering. Graphical abstract: Tissue engineered heart valves are constructed for the purpose of designing replacement heart valves (most often from decellularized tissues or polymer scaffolds) as well as for generating models of valve disease. The disease models, often fabricated using either natural or synthetic gel materials, enable investigators to elucidate disease mechanisms in the effort to identify new therapies. Highlights: Heart valve disease is a major cause of cardiovascular morbidity and mortality. Tissue-engineered valves would overcome the issues with current valve replacements. Novel biomaterials and cell seeding methods are being developed for these valves. Tissue-engineered models allow valve disease pathobiology to be studied in 3D. In these models, natural and synthetic polymers mimic the extracellular matrix.